2006
DOI: 10.1161/01.res.0000199263.67107.c0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Hyaluronic Acid Synthase Isoforms in Human Saphenous Vein Smooth Muscle Cells

Abstract: Abstract-Autologous saphenous vein bypass grafts (SVG) are frequently compromised by neointimal thickening and subsequent atherosclerosis eventually leading to graft failure. Hyaluronic acid (HA) generated by smooth muscle cells (SMC) is thought to augment the progression of atherosclerosis. The aim of the present study was (1) to investigate HA accumulation in native and explanted arterialized SVG, (2) to identify factors that regulate HA synthase (HAS) expression and HA synthesis, and (3) to study the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 44 publications
0
29
1
Order By: Relevance
“…Moreover, it is to be considered that young cells for the in vitro data came from a young, but mature donor whereas RNA for the in vivo experiments came from fetal tissues. Previous work showed that HAS1 together with HAS2 are the more abundant HAS isoforms expressed in saphenous vein, whereas SMCs isolated from the same vessel expressed mainly HAS2 and HAS3 (41). Even if a clear correlation is not reported in the literature between age and GAG content in the ECM of vessels (30), other studies reported an age increase of HA in aorta bifurcation (42) and in cerebral arteries (43).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, it is to be considered that young cells for the in vitro data came from a young, but mature donor whereas RNA for the in vivo experiments came from fetal tissues. Previous work showed that HAS1 together with HAS2 are the more abundant HAS isoforms expressed in saphenous vein, whereas SMCs isolated from the same vessel expressed mainly HAS2 and HAS3 (41). Even if a clear correlation is not reported in the literature between age and GAG content in the ECM of vessels (30), other studies reported an age increase of HA in aorta bifurcation (42) and in cerebral arteries (43).…”
Section: Discussionmentioning
confidence: 95%
“…In SMCs, HAS2 silencing by siRNA decreased cell proliferation (van den Boom et al 2006). Moreover, HAS2 expression was modulated by pharmacological treatments (Sussmann et al 2004), indicating a fine control of the expression of this enzyme.…”
Section: Has2 Abrogation Reduces Ha Synthesis In Aosmcsmentioning
confidence: 99%
“…Cells treated with PMA, IL-1␤, or PDGF-BB increase the amount of HA released into the culture medium (29,54,55), whereas treating cells with 4-MU decreases synthesis of HA (56). We tested the effects of these compounds on HAS activity in the PM and CM fractions.…”
Section: Effects Of 4-mu Pma Il-1␤mentioning
confidence: 99%